1999
DOI: 10.1080/096374899101283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coffee oil and its unsaponifiable fraction on plasma cholesterol level in female rats

Abstract: The present study was conducted to identify the cholesterol-raising factor in coffee oil besides the other two well-known diterpenes, cafestol and kahweol. Female rats fed coffee oil for 4 weeks showed significantly higher level of plasma cholesterol (P < 0.01) and triacylglycerols (P < 0.01). Feeding unsaponifiable lipids of coffee oil caused significant decrease in plasma cholesterol; however, increase in triacylglycerol was observed. Rats given beta-sitosterol showed increase in plasma triacylglecerol and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Little is known with certainty about the physiological effects of coffee, but a bewildering array of health and mood effects are attributed to it. In addition to the action of caffeine, it has been demonstrated that the lipid fraction of coffee, which includes two bioactive diterpenes, kafestol and kahweol, is able to increase low‐density lipoprotein and total serum cholesterol 2 . The presence of these substances depends on both the variety of coffee and the extraction procedure used for preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known with certainty about the physiological effects of coffee, but a bewildering array of health and mood effects are attributed to it. In addition to the action of caffeine, it has been demonstrated that the lipid fraction of coffee, which includes two bioactive diterpenes, kafestol and kahweol, is able to increase low‐density lipoprotein and total serum cholesterol 2 . The presence of these substances depends on both the variety of coffee and the extraction procedure used for preparation.…”
Section: Introductionmentioning
confidence: 99%